![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3√2 - 5√18 + 6√72 - 4√98 = 3√2-5.3√2+6.2.3√2-4.7/3.3√2
= 3√2(1-5+12-28/3)
= 3√2.(-4/3)
= -4√2
![](https://rs.olm.vn/images/avt/0.png?1311)
4( 3x + 4 )2 + 2x( 2x - 5 )( 2x + 5 ) - ( 2x + 3 )2
= 4( 9x2 + 24x + 16 ) + 2x( 4x2 - 25 ) - ( 4x2 + 12x + 9 )
= 36x2 + 96x + 64 + 8x3 - 50x - 4x2 - 12x - 9
= 8x3 + ( 36x2 - 4x2 ) + ( 96x - 50x - 12x ) + ( 64 - 9 )
= 8x3 + 32x2 + 34x + 55
![](https://rs.olm.vn/images/avt/0.png?1311)
\(c,9x^4+4x^2y^4-12x^3y^2=x^2\left(9x^2-12xy^2+4y^4\right)=x^2\left(3x-2y^2\right)^2\\ d,-x^3+8y^3-12xy^2+6x^2y=-\left(x-2y\right)^2\\ f,\left(2x-1\right)^2+\left(2-4x\right)\left(x+1\right)+\left(x+1\right)^2\\ =\left(2x-1\right)^2-2\left(2x-1\right)\left(x+1\right)+\left(x+1\right)^2\\ =\left(2x-1-x-1\right)^2=\left(x-2\right)^2\)
\(d,16x^2y^2-x^4y^2-16y^2\\ =-y^2\left(x^4-16x^2+16\right)\\ =-y^2\left[\left(x^2-8\right)^2-48\right]\\ =-y^2\left(x^2-4\sqrt{3}-8\right)\left(x^2+4\sqrt{3}-8\right)\\ e,27x^3-64y^3+36xy\left(4y-3x\right)\\ =27x^3-64y^3+144xy^2-108x^2y\\ =\left(3x-4y\right)^3\\ g,a^4+2a^3+5a^2+4a+4\\ =\left(a^4+2a^3+a^2\right)+\left(a^2+4a+4\right)\\ =a^2\left(a+1\right)^2+\left(a+2\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (2x+1)^2+2(4x^2-2)+(2x-1)^2=4x2+4x+1+8x2-4+4x2-4x+1=16x2-2
Lớp 8 có này ?? :D ??